Hasidic studies : essays in history and gender - Rapoport-Albert, Ada (The Littman library of Jewish civilization, 2018)
Ada Rapoport-Albert has been a key partner in the profound transformation of the history of hasidism that has taken shape over the past few decades. The essays in this volume show the erudition and creativity of her contribution. Written over a period of forty years, they have been updated with regard to significant detail and to take account of important works of scholarship written after they were originally published.